Project management: how to make projects more successful and the role of AI - Nieto-Rodriguez, Antonio (Henry Stewart Talks, 2023)
Project management, Project success, Leadership, Organizational politics, Executive support, Emotional intelligence, AI, Data management, Trust, Risk management